An Outcome of Gender Subjugation: Analyzing Major Female Characters in Khaled Hosseini’s, ‘A Thousand Splendid Suns’ - Humagain, Sumargi (International Research Journal of MMC, 2025)
This research explores the women's roles, their position, and the men’s attitudes towards them in the Afghan society as reflected in Khaled Hosseini’s A Thousand Splendid Suns (2007) with reference to the political disorder, the socio-cultural structures and the exercise of the male- supremacy in the family. It exposes the patriarchal manacles over the female characters, their journey from the subjugated status to the realization of being stereotyped and making revolutionary stage. Based on the qualitative approach, the feministic tool has been applied for the textual analysis. By enduring the various obstacles contradictory to the feminism such as the sexual maltreatment, the banishment, the early marriage, the polygamy, the political anarchy, Taliban dogmas, the male atrocities, the research findings justify the repressive condition of the Afghan women, and how eventually they succeed to unshackle themselves through uprising, struggle and harmony.